(untitled) (International Journal of Physiotherapy, 2025)
Background: The pelvic floor muscles (PFM) aid in maintaining anal and urinary continence while supporting the pelvic organs. The strain that pregnancy and childbirth place on these muscles frequently results in pelvic floor dysfunction (PFD). The number of births and the delivery procedure are two examples of factors that can impact this disease. Establishing a link between pelvic floor dysfunction in postpartum women and parity and delivery method was the aim of the study. Methods: In the present observational study, 60 postpartum women between the ages of 20 and 35 were evaluated 6 to 12 months after giving birth. Both written informed consent and ethical approval were acquired. Pelvic floor muscle strength was evaluated using the Oxford grading scale and vaginal palpation, and PFD symptoms were identified using the Australian Pelvic Floor Questionnaire. Statistical analysis was performed to find correlations. Results: A significant relationship was found between pelvic floor dysfunction, delivery mode, and the number of births (p = 0.002). The Oxford scale with PFD and the Australian Pelvic Floor Questionnaire showed a significant correlation (p = 0.001). Significant non-linear relationships between PFD and muscle strength scores, and between PFD and specific questionnaire items, were found at the 5% significance level. Conclusion: Pelvic floor dysfunction is substantially correlated with both the number of births and the delivery method. To reduce the impact of PFD on women’s health care, these results highlight the necessity of early postpartum screening and rehabilitation approaches.